Ús de les preposicions «a/en» davant els noms propis de lloc. Segles XIII-XVI - Cabanes, Vicent (Caplletra. Revista Internacional de Filologia, 2015)
Using a large amount of documentation from the 13th to 16th centuries, the author demonstrates that in general the preposition «en» indicated placement or permanence in place names, whereas «a» indicated motion towards a place.